2018
DOI: 10.3389/fphar.2018.01151
|View full text |Cite
|
Sign up to set email alerts
|

P311, Friend, or Foe of Tissue Fibrosis?

Abstract: P311 was first identified by the group of Studler et al. (1993) in the developing brain. In healthy, but mainly in pathological tissues, P311 is implicated in cell migration and proliferation. Furthermore, evidence in models of tissue fibrosis points to the colocalization with and the stimulation of transforming growth factor β1 by P311. This review provides a comprehensive overview on P311 and discusses its potential as an anti-fibrotic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…The authors found several muscular structural proteins like the MYH genes MYH1, MYH4, and MYH7 to be downregulated in PCS transcriptomes. The atrophy marker FBXO32 (MAFbx) was significantly overexpressed along with a clearly decreased expression of the yet unknown P311 protein (5), later identified as trans-differentiation regulator NREP which is known to be responsible for cell differentiation (59). The question whether muscle atrophy was cause or effect of impaired muscle maturation remained unanswered.…”
Section: Genetic Characterization Of the Splay Leg Syndromementioning
confidence: 99%
“…The authors found several muscular structural proteins like the MYH genes MYH1, MYH4, and MYH7 to be downregulated in PCS transcriptomes. The atrophy marker FBXO32 (MAFbx) was significantly overexpressed along with a clearly decreased expression of the yet unknown P311 protein (5), later identified as trans-differentiation regulator NREP which is known to be responsible for cell differentiation (59). The question whether muscle atrophy was cause or effect of impaired muscle maturation remained unanswered.…”
Section: Genetic Characterization Of the Splay Leg Syndromementioning
confidence: 99%
“…P311, with the official gene symbol NERP (neuronal regeneration related protein), is a highly conserved 8-kDa intracellular protein. The 68-amino acid sequence of P311 contains a PEST domain (rich in Pro, Glu, Ser, and Thr) in the N-terminus (Stradiot et al, 2018). The domain is also in short-lived proteins such as transcription factors, cytokines and signal molecules, which implies that P311 might belong to one of the protein families (Sommer and Wolf, 2014; Varshavsky, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…NREP is thought to stimulate the expression of TGF-β1 by promoting the methylation of the NREP promoter and activating the TGF- β 1 5′/3′ UTR ( Li et al, 2016 ). Recent studies have revealed that NREP promotes renal fibrosis via the TGF-β1 signaling pathway and that the deletion of NREP results in delayed burn wound healing ( Stradiot et al, 2018 ). The process of tumor development has been frequently compared to wound healing owing to several shared molecular and biological processes, including neovascularization, ECM remodeling, and fibrosis ( Chang et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%